Simplify 2sqrt27+3sqrt122√27+3√12? Prealgebra Exponents, Radicals and Scientific Notation Square Root 1 Answer Shwetank Mauria Jun 22, 2017 2sqrt27+3sqrt12=12sqrt32√27+3√12=12√3 Explanation: 22 square root of 2727 plus 33 square root of 1212 can be written as 2sqrt27+3sqrt122√27+3√12 = 2sqrt(3xx3xx3)+3sqrt(2xx2xx3)2√3×3×3+3√2×2×3 = 2sqrt(ul(3xx3)xx3)+3sqrt(ul(2xx2)xx3) = 2xx3xxsqrt3+3xx2xxsqrt3 = 6sqrt3+6sqrt3 = (6+6)sqrt3 = 12sqrt3 Answer link Related questions How do you simplify (2sqrt2 + 2sqrt24) * sqrt3? How do you simplify sqrt735/sqrt5? How do you rationalize the denominator and simplify 1/sqrt11? How do you multiply sqrt[27b] * sqrt[3b^2L]? How do you simplify 7sqrt3 + 8sqrt3 - 2sqrt2? How do you simplify sqrt468 ? How do you simplify sqrt(48x^3) / sqrt(3xy^2)? How do you simplify sqrt ((4a^3 )/( 27b^3))? How do you simplify sqrt140? How do you simplify sqrt216? See all questions in Square Root Impact of this question 1674 views around the world You can reuse this answer Creative Commons License